Visualizing Labrador: Maps, Photographs, and Geographical Naming in Mina Hubbard’s A Woman’s Way through Unknown Labrador - Roy, Wendy (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2004)
Mina Hubbard's 1908 account of her travels along the Nascaupee and George Rivers made lasting contributions to the cartography, ethnography, and toponymy of northern Labrador . Although her motives for undertaking the expedition were relational — her husband had died two years earlier in attempting the trip — her wish to be viewed as an explorer necessitated the adoption of masculine models of legitimacy. The maps and photographs accompanying Hubbard's narrative, while remarkable in demonstrating her unique personalization and domestication of the landscape, still encompass the explorer's conventional obligation to portray himself (or herself) as the first to arrive at key points along his (or her) journey, and the first to convey geographical or ethnological information to outsiders.